PRRSV-2 nsp2 Ignites NLRP3 inflammasome through IKKβ-dependent dispersed trans-Golgi network translocation. - Lujie Zhang; Yanni Gao; Haoran Zhou; Xiao Liang; Xiaolin Jiang; Wenqin Gong; Yangyang Sun; Desheng Zhang; Xianwei Wang; Hans Nauwynck; Juan Bai; Ping Jiang (PLoS Pathogens)
The NLRP3 inflammasome is a fundamental component of the innate immune system, yet its excessive activation is intricately associated with viral pathogenesis. Porcine reproductive and respiratory syndrome virus type 2 (PRRSV-2), belonging to the family Arteriviridae, triggers dysregulated cytokine release and interstitial pneumonia, which can quickly escalate to acute respiratory distress and death. However, a mechanistic understanding of PRRSV-2 progression remains unclear. Here, we screen that PRRSV-2 nsp2 activates the NLRP3 inflammasome, thereby instigating a state of hyperinflammation. Mechanistically, PRRSV-2 nsp2 interacts with the nucleotide-binding and oligomerization (NACHT) domain of NLRP3, augmenting IKKβ recruitment to driving NLRP3 translocation to the dispersed trans-Golgi network (dTGN) for oligomerization. This process facilitates ASC polymerization, culminating in the activation of the NLRP3 inflammasome. In addition, the IKKβ-dependent NLRP3 translocation to the dTGN is pivotal for pseudorabies virus (PRV) and encephalomyocarditis virus (EMCV)-induced inflammatory responses. Collectively, these results elucidate a novel mechanism of NLRP3 inflammasome activation during PRRSV-2 infection, providing valuable insights into PRRSV-2 pathogenesis.